Identification of Cytolytic Vaginosis Versus Vulvovaginal Candidiasis. Issue 2 (April 2015) - Hu, Zhengqiang; Zhou, Wei; Mu, Liyuan; Kuang, Linghan; Su, Min; Jiang, Yongmei
<x xml:space="preserve">Abstract</x> Objective This study aimed to observe the morphological characteristic of vaginal discharge in patients with cytolytic vaginosis (CV) under the microscope and to identify it in patients with CV and in patients with vulvovaginal candidiasis (VVC). Methods A total of 108 subjects including 21 healthy women, 33 patients with CV, and 54 patients with VVC were enrolled in the present morphological study. Vaginal discharge was collected and made into smear. The morphological characteristics of these vaginal smears with Gram staining were observed under the microscope. The smears were assessed for the quantity of lactobacilli, epithelial cell morphology, and the absence or presence of Candida species, Trichomonas vaginalis, and clue sells. Results First, the age, the level of education, and especially the status of pregnancy of patients with CV were significantly different from those of the patients with VVC. Second, the morphological characteristics of patients with CV consisted of overgrowth of lactobacilli, the presence of naked nuclei and fragments of the epithelial cells, a paucity of leukocytes, and the absence of Candida species and other pathogens. However, the morphological characteristic of patients with VVC consisted of the presence or absence of lactobacilli and the presence of normal epithelial cells, candidal spores, blastospores, hyphae, or other pathogens such as T. vaginalis and Gardnerella vaginalis. Conclusions Both CV and VVC can be identified based on the quantity of lactobacilli, the morphology of the epithelial cells, and the absence or presence of Candida species and other pathogens, and the misdiagnosis of CV as VVC can be avoided.